Development of Sharia Based Local Wisdom Business at Society of Mandailing Natal - Asrul Hamid; Khairul Bahri Nasution; Resi Atna Sari Siregar; Jannus Tambunan (LAA MAISYIR: Jurnal Ekonomi Islam, 2022)
Integration of Islam with local wisdom in business development in Mandailing Natal Regency as an effort to improve the economy and welfare by rejecting the concept of exploitation and discrimination but prioritizing the value of benefit in the midst of the proliferation of franchised businesses. This study aims to analyze the development of sharia-based local wisdom business in Mandailing Natal Regency. This research method uses a qualitative descriptive approach. Sources of data are described from the results of observations, interviews, and documents as well as relevant references to understand socio-cultural both in attitudes, motivations and people's expectations related to business development by analyzing data using qualitative methods. The results show that business development by integrating Islamic values ​​with local wisdom of Mandailing Natal referring to the philosophy of Dalihan Na Tolu, Marsialap ari Marsalapari and Poda Na Lima, is a strategic step in developing a business so that it can compete with franchise businesses, in line with the adage “Hombardo adat dohot worship as a way of life. Steps that need to be developed are regulations, new innovations and management and marketing strategies that are tailored to the needs of the community and market and according to sharia principles as an effort to realize a balance of welfare and happiness in this world and the hereafter.